1996
DOI: 10.1002/(sici)1097-4660(199612)67:4<350::aid-jctb564>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Microcrystalline-Cellulose Hydrolysis with Concentrated Sulphuric Acid

Abstract: The effects of temperature (25–40°C), H2SO4 concentration (31–70% (w/v)) and the acid/substrate relationship (1–5 cm3 of H2SO4 per g−1 of cellulose) on the solubilization rate of microcrystalline cellulose and on the glucose production rate have been analysed. The solubilization process was by determining reducing groups present in solution. For acid/substrate relationships of more than 1 cm3 g−1 and H2SO4 concentrations of greater than 62% (w/v), the acid promoted the total solubilization of the cellulose in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
75
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 5 publications
(1 reference statement)
5
75
0
Order By: Relevance
“…To overcome the first challenge, room temperature ionic liquids such as EMIMAc can be employed as environmentally benign solvent, which is safer and easier to handle than traditionally used solvents such as carbon disulphide [9], sulphuric acid [10] and N-methylmorpholine-N-oxide (NMMO) [11]. A number of researchers have used ionic liquids for fibre stretching/spinning of cellulose [12][13][14][15][16][17][18], wool [19,20], chitin [21][22][23][24] and other natural polymers [25][26][27][28], as well as composite fibres of cellulose [8,29].…”
supporting
confidence: 92%
“…To overcome the first challenge, room temperature ionic liquids such as EMIMAc can be employed as environmentally benign solvent, which is safer and easier to handle than traditionally used solvents such as carbon disulphide [9], sulphuric acid [10] and N-methylmorpholine-N-oxide (NMMO) [11]. A number of researchers have used ionic liquids for fibre stretching/spinning of cellulose [12][13][14][15][16][17][18], wool [19,20], chitin [21][22][23][24] and other natural polymers [25][26][27][28], as well as composite fibres of cellulose [8,29].…”
supporting
confidence: 92%
“…Water was then removed in 75 vacuo at 50 ºC, usually for 48 h. ILs were obtained as colourless viscous liquids. Composition and purity of the ILs were confirmed by 1 H-NMR, 13 C-NMR and mass spectroscopy; these data are given in the electronic supplementary information.…”
mentioning
confidence: 99%
“…These early investigations showed that at room or lower temperatures, the sulfuric acid with concentrations greater than 63 wt.% caused swelling and dissolving of cellulose samples that was accompanied by hydrolysis process. Increased temperatures of the acidic treatment promoted both to hydrolysis and dissolving of cellulose [1,2] . At increased concentrations >63wt.% molecules of sulfuric acid are capable to break the hydrogen bonds and penetrate into noncrystalline and crystalline domains of the polymer with forming of the complexes [1] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the other papers [1,2,9,20,21] it was found that, the sulfuric acid at concentrations greater than 63-64 wt.% causes swelling and dissolving of cellulose samples. When the acidic solution of cellulose was diluted with water the soluble cellulose was regenerated and precipitated in a form of low molecular amorphized flocs having crystalline polymorph of CII-type [9,20,21,22] .…”
Section: Introductionmentioning
confidence: 99%